Therapeutic work to enhance parental mentalizing for parents with ACEs to support their children's mental health: A theoretical and clinical review - Dollberg, Daphna G.; Hanetz-Gamliel, Keren (Frontiers in Child and Adolescent Psychiatry, 2023)
This review outlines the literature concerning the impact of adverse childhood experiences (ACEs) on parenting, focusing on how childhood trauma in parents might impede the development of adaptive parental mentalizing skills. Non-adaptive parental mentalizing may lead to non-mentalizing cycles between parents and children, which can put the child’s mental health at risk. When parents who have endured ACEs have to cope with their children’s mental health problems, they may have to deal with a double dose of parental stress related to their own traumatic history and their children’s emotional difficulties. This heightened parental stress may further shake the parents’ mentalizing skills. In line with this special issue’s topic, we propose the promoting and restoring of parental mentalizing as a treatment goal for parents who have endured ACEs and whose children face mental health difficulties. We review the empirical and clinical evidence regarding the benefits of effective parental mentalizing and the availability of techniques to enhance it. We argue that working therapeutically and focusing on supporting and advancing parental mentalizing is an effective and feasible treatment goal with parents who endured ACEs. We demonstrate how we use these interventions through fictional vignettes from our therapeutic work and offer recommendations for clinical work with parents with traumatic histories.